2016
DOI: 10.1007/s11356-016-7236-6
|View full text |Cite
|
Sign up to set email alerts
|

Combination of biochar amendment and phytoremediation for hydrocarbon removal in petroleum-contaminated soil

Abstract: Remediation of soils contaminated with petroleum is a challenging task. Four different bioremediation strategies, including natural attenuation, biochar amendment, phytoremediation with ryegrass, and a combination of biochar and ryegrass, were investigated with greenhouse pot experiments over a 90-day period. The results showed that planting ryegrass in soil can significantly improve the removal rate of total petroleum hydrocarbons (TPHs) and the number of microorganisms. Within TPHs, the removal rate of total… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
16
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(20 citation statements)
references
References 54 publications
3
16
1
Order By: Relevance
“…Additionally, in biochar amended soils, the TPH concentration was found to be 15-10 % lower compared to un-amended soil samples, confirming that biochar was able to effectively lock the organic contaminants. Comparable to previous studies, compost addition was overall more efficient in promoting biodegradation than biochar (Cai et al, 2010;Han et al, 2016;Zhang et al, 2010).…”
Section: Soil Characteristicscontrasting
confidence: 65%
“…Additionally, in biochar amended soils, the TPH concentration was found to be 15-10 % lower compared to un-amended soil samples, confirming that biochar was able to effectively lock the organic contaminants. Comparable to previous studies, compost addition was overall more efficient in promoting biodegradation than biochar (Cai et al, 2010;Han et al, 2016;Zhang et al, 2010).…”
Section: Soil Characteristicscontrasting
confidence: 65%
“…Although several plant species have been shown to be effective for the removal of PHs from contaminated soils [1,12], the improvement in the effectiveness of phytoremediation is still a challenge. It has been well documented those microbial activities and physicochemical properties of soil have a marked impact on the effectiveness of phytoremediation of PHs [13,14]. A vast variety of microbial communities such as fungi, algae and bacteria take part in the complete mineralization of PHs [15].…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, the plants in association with microbes show better physical and physiological responses (i.e., seedling emergence, root/shoot biomasses, root/shoot length and chlorophyll contents etc.) and enhance the PHs degradation [13,29,30].…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that plants are effective in degradation, transformation, assimilation, metabolism and detoxification of hazardous pollutants from soils (Cai et al, 2010). The efficacy of plants for removal of crude oil pollutants has already been established by several workers around the globe (Han et al, 2016;Cheng et al, 2017). For example, some plants such as tall fescue, fire phoenix and maize have also been used for remediation of crude oil contaminated soil in recent past (Liu et al, 2014a,b;Liao et al, 2016).…”
Section: Introductionmentioning
confidence: 99%